MUSCULOSKELETAL AND CONNECTIVE TISSUE DISEASES: DISABILITY IN THE IRKUTSK REGION IN 2013–2015 - I. L. Petrunko; L. V. Menshikova; N. V. Sergeeva; S. S. Bichev; A. A. Cherkasova (Научно-практическая ревматология, 2017)
Objective: to study the rates of primary disability due to musculoskeletal and connective tissue diseases (MSCTD) in the Irkutsk Region in 2013–2015 (in relation to age, gender, and urban or rural residence) and its nosological pattern.Material and methods. A continuous method was used to analyze the database on the newly recognized as disabled due to MSCTD in the Irkutsk Region in 2013–2015. The rates were calculated per 10,000 adult population; the pattern was estimated as a percent.Results and discussion. The rates of primary disability due to MSCTD in the Irkutsk Region were higher than those in the Russian Federation as a whole. Its reduction from 10.4 per 10,000 population in 2013 to 10.3 in 2014 and to 5.9 in 2015 was noted in the adults. Osteoarthritis headed the list of the causes of primary disability in the adults (45.5% in 2015) whereas dorsopathies did in the able-bodied (45.9% in 2015, 47.1% in 2014, and 48.2% in 2013). Osteoarthritis ranked first in the retirement-aged (61.5% in 2015, 75.1% in 2014, and 72% in 2013); it occupied the second place in the able-bodied (31.6% in 2015, 36.3% in 2014, and 38.2% in 2013). Rheumatoid arthritis was third among both the able-bodied and the retirement-aged. Higher disability rates were observed in the urban residents over all the years. The women became disabled more frequently than the men. In 2015, the primary disability rates among the men were 5.2, those among the women were 6.4 per 10,000 population; these were 9.2 and 19.4 and 8.4 and 12.1 in 2014 and 2013, respectively. The lower rates of disability due to MSCTD may be attributable to both the greater availability of high-quality and high-tech medical care for patients and the changes in normative documents on disability criteria.